A decomposition approach to dual shuttle automated storage and retrieval systems. (November 2016) - Wauters, Tony; Villa, Fulgencia; Christiaens, Jan; Alvarez-Valdes, Ramon; Vanden Berghe, Greet
Highlights: Heuristic control policies for dual shuttle automated storage and retrieval systems are studied. A decomposition approach employing both exact and heuristic components is presented and validated. A fast metaheuristic suitable for real-world sized AS/RS problems is proposed. Abstract: Automated Storage and Retrieval Systems (AS/RS) have become vital in today's distribution and production environments, however it remains necessary to equip them with more efficient operational control policies. Motivated by real situations encountered by companies employing AS/RS, the present paper studies a miniload AS/RS system, with a dual shuttle crane in which a set of storage and retrieval requests must be scheduled such that the prioritized waiting time is minimized. Dual shuttle cranes have received minimal academic attention and thus continue to pose new problems that must be solved. The miniload AS/RS problem is addressed by decomposing it into a location assignment and sequencing problem. Different heuristic strategies are introduced for making the assignments, while a general mathematical model and efficient branch and bound procedure are proposed for optimizing the sequence. Additionally, a fast metaheuristic capable of solving larger instances is also developed. A set of real-world based benchmarks with varying characteristics is generated to evaluate the proposed methods. Very small instances prove the only for which optimal sequences are found in reasonable calculation time. Experimental results demonstrate the effectiveness of the heuristic decomposition method.